The Effect of Jingle Exposure in Television Advertising on Brand Awareness in the Elaboration Likelihood Model - Mustikasari, Ratih Pandu; Dian Hutami Rahmawati; Heidy Arviani (LPPM Stikosa - AWS, 2023)
Message processing is a very important part of the communication process. The Elaboration Likelihood Model (ELM) is a communication theory that is in the sociopsychological tradition and focuses on message processing. ELM sees that messages are processed by individuals through two routes, namely central and peripheral. This theory is used to analyze the information processing of respondents to exposure to Oreo advertising jingles on brand awareness. According to Aaker (in Chernatony, McDonald and Wallace, 2011, p. 455), brand awareness itself has four important indicators, namely brand recognition, brand recall, brand dominance and brand knowledge. This research was conducted by experimental method. The results of the hypothesis test show that there is a significant influence between jingles and brand awareness. The path used by respondents in processing the information in this jingle is the peripheral route.